Nuclear Export of the Human Cytomegalovirus Tegument Protein pp65 Requires Cyclin-Dependent Kinase Activity and the Crm1 Exporter - Sanchez, Veronica (American Society for Microbiology (ASM), 2007)
We have previously shown that treatment of human cytomegalovirus-infected cells with the cyclin-dependent kinase (cdk) inhibitor roscovitine has significant effects on several stages of the virus life cycle depending on the time of addition (V. Sanchez, A. K. McElroy, J. Yen, S. Tamrakar, C. L. Clark, R. A. Schwartz, and D. H. Spector, J. Virol. 78:11219-11232, 2004; V. Sanchez and D. Spector, J. Virol. 80:5886-5896, 2006). In this report, we add to these findings by demonstrating alterations in the phosphorylation and localization of pp65 (UL83) in cells treated with roscovitine. We observed that inhibition of cdk activity causes the retention of pp65 within the nucleus at late times postinfection. At the same time, we observed a change in the phosphorylation pattern of the protein. Interestingly, mutation of potential cdk phosphorylation sites did not affect the ability of pp65 to localize to the nucleus or to relocalize to the cytoplasm late in infection. However, we found that the cytoplasmic accumulation of pp65 late in infection was sensitive to the Crm1 inhibitor leptomycin B.